1999
DOI: 10.1029/1999gl900141
|View full text |Cite
|
Sign up to set email alerts
|

The September 26, 1997 Colfiorito, Italy, earthquakes: Modeled coseismic surface displacement from SAR interferometry and GPS

Abstract: Abstract.The largest events of the 1997 UmbriaMarche seismic sequence were the two September 26 earthquakes of Mw=5.7 (00:33 GMT) and Mw=6.0 (09:40 GMT), which caused severe damage and ground cracks in a wide area around the epicenters. We created an ERS-SAR differential interferogram, where nine fringes are visible in and around the Colfiorito basin, corresponding to 25 cm of coseismic surface displacement. GPS data show a maximum horizontal displacement of (14 + 1.8) cm and a maximum subsidence of (24 + 3) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 8 publications
4
92
1
1
Order By: Relevance
“…Fault slip for the two Colfiorito main shocks of September 26 reveals maximum amplitudes of 36 cm and 65 cm, respectively, as reported by HUNSTAD et al (1998) and STRAMONDO et al (1999). Although these shocks did not produce primary surface ruptures, the observed ground breaks (CINTI et al, 1999) identified a diffuse surface deformation along a 10-km-wide belt whose strike is in agreement with the The main shock occurred at 09:40 (M W ¼ 6.0; M 0 ¼ 1.26 · 10 25 dyne-cm) and accounts for about 50% of the total moment release in the sequence (EKSTRO¨M et al, 1998).…”
Section: The 1997 Umbria-marche Italy Earthquake Sequencesupporting
confidence: 50%
“…Fault slip for the two Colfiorito main shocks of September 26 reveals maximum amplitudes of 36 cm and 65 cm, respectively, as reported by HUNSTAD et al (1998) and STRAMONDO et al (1999). Although these shocks did not produce primary surface ruptures, the observed ground breaks (CINTI et al, 1999) identified a diffuse surface deformation along a 10-km-wide belt whose strike is in agreement with the The main shock occurred at 09:40 (M W ¼ 6.0; M 0 ¼ 1.26 · 10 25 dyne-cm) and accounts for about 50% of the total moment release in the sequence (EKSTRO¨M et al, 1998).…”
Section: The 1997 Umbria-marche Italy Earthquake Sequencesupporting
confidence: 50%
“…Meghraoui et al [1999] suggested that the seismogenic low-angle normal faults were controlled by preexisting thrusts and branched at high-angle near the ground surface. Indeed, the analysis of DInSAR images [Stramondo et al 1999] and GPS measurements [Hunstad et al, 1999] suggest that the ruptures stopped very close to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, one of the four GPS benchmarks in the epicentral area measured about 14-cm horizontal and about 24-cm vertical movements. Either GPS or DInSAR has been the input data to an inversion modeling program that has provided an estimation of the fault parameters (Stramondo et al 1999) and the distribution of the slip over the fault plane (Fig. 4).…”
Section: Umbria-marche (1997)mentioning
confidence: 99%